Maternal Deprivation Exacerbates the Response to a High Fat Diet in a Sexually Dimorphic Manner - Mela, Virginia (Public Library of Science, 2012)
Maternal deprivation (MD) during neonatal life has diverse long-term effects, including affectation of metabolism. Indeed, MD for 24 hours during the neonatal period reduces body weight throughout life when the animals are maintained on a normal diet. However, little information is available regarding how this early stress affects the response to increased metabolic challenges during postnatal life. We hypothesized that MD modifies the response to a high fat diet (HFD) and that this response differs between males and females. To address this question, both male and female Wistar rats were maternally deprived for 24 hours starting on the morning of postnatal day (PND) 9. Upon weaning on PND22 half of each group received a control diet (CD) and the other half HFD. MD rats of both sexes had significantly reduced accumulated food intake and weight gain compared to controls when raised on the CD. In contrast, when maintained on a HFD energy intake and weight gain did not differ between control and MD rats of either sex. However, high fat intake induced hyperleptinemia in MD rats as early as PND35, but not until PND85 in control males and control females did not become hyperleptinemic on the HFD even at PND102. High fat intake stimulated hypothalamic inflammatory markers in both male and female rats that had been exposed to MD, but not in controls. Reduced insulin sensitivity was observed only in MD males on the HFD. These results indicate that MD modifies the metabolic response to HFD intake, with this response being different between males and females. Thus, the development of obesity and secondary complications in response to high fat intake depends on numerous factors.